Strain-induced room-temperature ferroelectricity in SrTiO3 membranes - Ruijuan Xu (Nature Portfolio, 2020)
Previous approach lacks the ability to produce large and continuously tunable strain states due to the limited number of available substrates. Here, the authors demonstrate strain-induced ferroelectricity in SrTiO3 membranes by laminating freestanding SrTiO3 films onto a stretchable polymer.